Peonidin‐3‐O‐glucoside and cyanidin increase osteoblast differentiation and reduce RANKL‐induced bone resorption in transgenic medaka. (26th October 2021) - Ren, Zhitao; Raut, Nishikant A.; Lawal, Temitope O.; Patel, Shital R.; Lee, Simon M.; Mahady, Gail B.
Abstract : Experimental and clinical studies suggest a positive impact of anthocyanins on bone health; however, the mechanisms of anthocyanins altering the differentiation and function of osteoblasts and osteoclasts are not fully understood. This work demonstrates that dietary anthocyanins and resveratrol increased proliferation of cultured human hFOB 1.19 osteoblasts. In addition, treatment of serum starvation of hFOB osteoblasts with anthocyanins and resveratrol at 1.0 μg/ml reduced apoptosis, the Bax/Bcl‐2 ratio, p53, and HDAC1 expression, but increased SIRT1/3 and PGC1α mRNA expression, suggesting mitochondrial and epigenetic regulation. In Sp7/osterix :mCherry transgenic medaka, peonidin‐3‐O‐glucoside and resveratrol increased osteoblast differentiation and increased the expression of Sp7/osterix . Cyanidin, peonidin‐3‐O‐glucoside, and resveratrol also reduced RANKL‐induced ectopic osteoclast formation and bone resorption in col10α1 :nlGFP/ rankl :HSE:CFP medaka in doses of 1–4 μg/ml. The results indicate that both cyanidin and peonidin‐3‐O‐glucoside have anabolic effects on bone, increasing osteoblast proliferation and differentiation, mitochondrial biogenesis, and by altering the osteoblast epigenome. Cyanidin and peonidin‐3‐O‐glucoside also reduced RANKL‐induced bone resorption in a transgenic medaka model of bone resorption. Thus, peonidin‐3‐O‐glucoside and cyanidin appear to both increase bone formation and reduce bone loss, suggesting that they be further investigated as potential treatments for osteoporosis and osteomalacia.